The Research Philosophies, Values, and Principles of Ontology, Epistemology, And Axiology in A State-Owned Holding Company - Abdullah , Edwin Hidayat; Sijabat, Rosdiana; Susilo, Wilhelmus Hary; Herusetya, Antonius (Journal of Ecohumanism, 2024)
A paradigm represents specific fundamental or metaphysical beliefs that formulate an entire system of ideas and refers to the paradigm as a set of systematic beliefs and research methods that accompany it. The paradigm is a worldview of state-owned enterprise business Holding and a way of thinking about and understanding the complexity of business facts related to the formation of strategies, business synergies, and business integration. Therefore, the paradigm is deeply rooted in sustainable business control based on orchestrating strategic activities in the business ecosystem to win sustainable business competition.